2000
DOI: 10.1086/308830
|View full text |Cite
|
Sign up to set email alerts
|

Observational Limits on Terrestrial‐sized Inner Planets around the CM Draconis System Using the Photometric Transit Method with a Matched‐Filter Algorithm

Abstract: A light curve of the eclipsing binary CM Draconis has been analyzed for the presence of transits of planets of size º2.5 Earth radii with periods of 60 days or less, and in coplanar orbits around the (R E ), binary system. About 400 million model light curves, representing transits from planets with periods ranging from 7 to 60 days, have been matched/correlated against these data. This process we call the "" transit detection algorithm ÏÏ or TDA. The resulting "" transit statistics ÏÏ for each planet candidat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 23 publications
0
69
0
Order By: Relevance
“…In this analysis the best detection method was found to be the modified matched filter approach of Doyle et al (2000). Revised work by Tingey (2003b) found that a modified version of the boxfitting least-squares method of Kovács et al (2002) gave better results.…”
Section: Candidate Selectionmentioning
confidence: 90%
“…In this analysis the best detection method was found to be the modified matched filter approach of Doyle et al (2000). Revised work by Tingey (2003b) found that a modified version of the boxfitting least-squares method of Kovács et al (2002) gave better results.…”
Section: Candidate Selectionmentioning
confidence: 90%
“…It is therefore not necessary to test the Bayesian. Moreover, the matched filter clearly performed better than the correlation and Deeg's approach (Doyle et al 2000), so the latter two can also be left out. Therefore, only the essential approaches will be included: the matched filter, which was determined to be the best in Paper I and the BLS, which was not implemented in the ideal fashion.…”
Section: Transit Detection Algorithmsmentioning
confidence: 98%
“…Several transit detection algorithms were proposed in the recent literature: Bayesian algorithms (Doyle et al 2000;Defaÿ et al 2001;Aigrain & Favata 2002), matched filters (Jenkins et al 1996), box-shaped transit finder (Aigrain & Irwin 2004), and the Box-fitting Least Squares (BLS) method (Kovács et al 2002). A theoretical comparison of these methods was proposed (Tingley 2003), which concluded that "no detector is clearly superior for all transit signal energies", but an optimized BLS algorithm still performs slightly better for shallower transits.…”
Section: Introductionmentioning
confidence: 99%